2007
DOI: 10.1073/pnas.0703774104
|View full text |Cite
|
Sign up to set email alerts
|

Free methionine-( R )-sulfoxide reductase from Escherichia coli reveals a new GAF domain function

Abstract: The reduction of methionine sulfoxide (MetO) is mediated by methionine sulfoxide reductases (Msr). The MsrA and MsrB families can reduce free MetO and MetO within a peptide or protein context. This process is stereospecific with the S-and R-forms of MetO repaired by MsrA and MsrB, respectively. Cell extracts from an MsrA ؊ B ؊ knockout of Escherichia coli have several remaining Msr activities. This study has identified an enzyme specific for the free form of Met-(R)-O, fRMsr, through proteomic analysis. The re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
141
1
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 129 publications
(148 citation statements)
references
References 49 publications
5
141
1
1
Order By: Relevance
“…Reduced and alkylated peptides were digested overnight at 37°C with trypsin. Peptides were separated by reverse phase chromatography and analyzed directly by electrospray ionization using a nanoelectrospray ionization source on a Bruker Esquire HCT ion trap mass spectrometer (27). MS/MS spectra were searched against the current release of the Mass Spectrometry Protein Sequence Data Base (obtained from the Imperial College London) using Mascot (36).…”
Section: Methodsmentioning
confidence: 99%
“…Reduced and alkylated peptides were digested overnight at 37°C with trypsin. Peptides were separated by reverse phase chromatography and analyzed directly by electrospray ionization using a nanoelectrospray ionization source on a Bruker Esquire HCT ion trap mass spectrometer (27). MS/MS spectra were searched against the current release of the Mass Spectrometry Protein Sequence Data Base (obtained from the Imperial College London) using Mascot (36).…”
Section: Methodsmentioning
confidence: 99%
“…To date, only one crystal structure of fRMsr, that from Escherichia coli, is available in the PDB (PDB code 1vhm) and its biochemical function and catalytic mechanism were reported to be unknown (Badger et al, 2005). The X-ray structure suggested that fRMsrs use Cys residues for catalysis and that the active site is enclosed in a small cavity (Lin et al, 2007). The enclosed cavity supports the apparent substrate specificity.…”
Section: Introductionmentioning
confidence: 99%
“…The fRMsr sequence is conserved in bacteria and yeast but is not found in humans (Lin et al, 2007). The overall folds show that MsrA, MsrB and fRMsr are unrelated.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations